AUDITORIA DE MODELOS BIM 4D EM CANTEIROS DE OBRAS DE CONSTRUTORAS DA CIDADE DE FORTALEZA-CE - Rocha, Paulo Henrique Gomes da; Silva, Raymundo Robson Gomes da; Silva Filho, Washington Bastos da; Barros Neto, José; Ramos, Mibson Michel Santiago (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In the construction of daily life, the project term is usually used to refer to a set of drawings and technical details in the various disciplines of engineering and serving north to the materialization of the building. However it is more than that, representing period defined in time and whose uniqueness and particularities differentiate it from any other, making it unique. In order to reduce interference and improve the activities at construction sites, BIM tools in 4D models are integrated into the sites, but it is necessary to observe whether this use is actually bringing productive advantages or is only a marketing tool. In this work, the process of planning and implementation of 4D models in construction sites of three companies in the field of construction and development of Fortaleza / CE has been audited and proposals have been made for improvement. An interview guide was prepared and submitted for production managers of their respective companies. After analyzing the responses, it was found the gaps between recommended in the literature and practiced in the company. Finally, improvements have been proposed in order to fill such gaps, which were mainly in training of manpower.